Impaired muscle uptake of creatine in spinal and bulbar muscular atrophy. Issue 7 (23rd June 2016) - Hijikata, Yasuhiro; Katsuno, Masahisa; Suzuki, Keisuke; Hashizume, Atsushi; Araki, Amane; Yamada, Shinichiro; Inagaki, Tomonori; Iida, Madoka; Noda, Seiya; Nakanishi, Hirotaka; Banno, Haruhiko; Mano, Tomoo; et al.
Abstract: Objective: The aim of this study was to explore the pathomechanism underlying the reduction of serum creatinine (Cr) concentrations in spinal and bulbar muscular atrophy (SBMA). Methods: We evaluated blood chemistries, motor function, and muscle mass measured by dual‐energy X‐ray absorptiometry in male subjects with SBMA ( n = 65), amyotrophic lateral sclerosis (ALS; n = 27), and healthy controls ( n = 25). We also examined the intramuscular concentrations of creatine, a precursor of Cr, as well as the protein and mRNA expression levels of the creatine transporter (SLC6A8) in autopsy specimens derived from subjects who had SBMA and ALS and disease controls. Furthermore, we measured the mRNA expression levels of SLC6A8 in cultured muscle cells (C2C12) transfected with the polyglutamine‐expanded androgen receptor (AR‐97Q). Results: Serum Cr concentrations were significantly lower in subjects with SBMA than in those with ALS ( P < 0.001), despite similar muscle mass values. Intramuscular creatine concentrations were also lower in with the autopsied specimen of SBMA subjects than in those with ALS subjects ( P = 0.018). Moreover, the protein and mRNA expression levels of muscle SLC6A8 were suppressed in subjects with SBMA. The mRNA levels of SLC6A8 were also suppressed in C2C12 cells bearing AR‐97Q. Interpretation: These results suggest that low serum Cr concentration in subjects with SBMA is caused by impaired muscle uptake of creatine in addition to being caused by neurogenic atrophy. Given that creatine serves as an energy source in skeletal muscle, increasing muscle creatine uptake is a possible therapeutic approach for treating SBMA.